2016
DOI: 10.1007/s00127-016-1242-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of fracture in patients with bipolar disorder: a nationwide cohort study

Abstract: Our study showed that patients with BD have a higher risk of subsequent fracture. Additional prospective clinical studies investigating the relationship between BD and fracture are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…Consistent with our findings of increased healthcare contacts due to bone fractures in adults, Su et al showed an increased risk of fractures in patients with BD compared with healthy controls . In addition, Hsu et al found that a BD diagnosis was an independent risk factor for bone‐fractures, regardless of sex, age, and comorbidities in a population of patients >16 years old . To our knowledge, this is the first study to investigate the incidence of bone fractures in children and adolescents diagnosed with BD, and in contrast to the findings in adults, children and adolescents did not have an increased incidence of bone fractures compared to PHCs.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings of increased healthcare contacts due to bone fractures in adults, Su et al showed an increased risk of fractures in patients with BD compared with healthy controls . In addition, Hsu et al found that a BD diagnosis was an independent risk factor for bone‐fractures, regardless of sex, age, and comorbidities in a population of patients >16 years old . To our knowledge, this is the first study to investigate the incidence of bone fractures in children and adolescents diagnosed with BD, and in contrast to the findings in adults, children and adolescents did not have an increased incidence of bone fractures compared to PHCs.…”
Section: Discussionsupporting
confidence: 89%
“…BD refers to a group of affective disorders in psychiatry, which is characterized by multiple depressive or manic episodes [35]. Recent data have revealed increased fracture risk in patients with BD [7,28,36]. Hsu et al [7] conducted a retrospective population-based cohort study and found that patients with BD have a higher risk of subsequent fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have revealed increased fracture risk in patients with BD [7,28,36]. Hsu et al [7] conducted a retrospective population-based cohort study and found that patients with BD have a higher risk of subsequent fracture. They demonstrated that BD was an independent risk factor for fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations